Influence of Geomagnetically Induced Currents on Three-Phase Power Transformers - Masoum, Mohammad; Moses, Paul (University of New South Wales, 2008)
A new nonlinear model has been adapted to include Geomagnetically Induced Currents (GIC) entering the neutrals of three-phase transformers. A time-domain nonlinear transformer model has been implemented under steady-state and transient GIC conditions (e.g., transformer inrush) to investigate the impact on power quality. The influence of three-limb core structures and their nonlinearities are included in the model. The resulting waveform harmonics in transformer voltages and currents are shown. In this contribution, transformer additional losses (fundamental and harmonics) and inrush currents in the presence of GIC have been computed and the sensitivity of transformer additional losses has been demonstrated.